Melitids (Crustacea: Amphipoda) of the genera Ceradocus and Mallacoota from Rodrigues Island (Indian Ocean) - Appadoo, Chandani; Myers, Alan A. (Zootaxa, 2006)
The present work represents a pioneer study on the family Melitidae from Rodrigues, Indian Ocean. Taxonomic descriptions and drawings are given for four new species of melitids namely Ceradocus shoalsi sp. nov., C. cotonensis sp. nov., C. oliveri sp. nov. and Mallacoota magnimerus sp. nov. A key to the Ceradocus species of the Mascarene Islands is provided. Mallacoota insignis (Chevreux) is reported for the first time from Rodrigues.